Analisis Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian Handphone Samsung (Studi Kasus Pada Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Widayat jati, Eko, Muzzakar Isa, SE., M.Si (2016)
This study aims to determine the effect of brand equity on purchase decisions samsung mobile phones and which factors most influence on the purchasing decision of Samsung mobile phones. The analysis tool used is multiple linear regression, by retrieving data using questionnaires the respondents Faculty of Economics and Business, University of Muhammadiyah Surakarta class of 2011 to 2015. This study refers to the positive approach, the approach which began the study with a hypothesis and then followed by hypothesis testing , Variable brand awareness and brand perception but not significantly influence the purchasing decision of Samsung mobile phones. While factors of brand associations and brand loyalty significantly influence the purchasing decision of Samsung mobile phones. The independent variables consisting of brand awareness, brand association, brand perception and brand loyalty together (simultaneously) significantly influence the purchase decision variables Samsung mobile phone. Where obtained F count equal to 14 937 with a significance level of 0.000. R square value in this study, that is equal to 0.386, meaning that 38.6% of Samsung mobile phone purchase decision variable can be explained by the variable of brand awareness, brand association, brand perception and brand loyalty, while the remaining 61.4% is explained by factors another. Thus the mobile phone manufacturer Samsung should have to pay attention to the brand association and brand loyalty products to consumers in order to dominate the market